Method for Diminishing the Adverse Effect of Anthropogenic Heavy Metal Pollution on Poultry Meat Products - TEMIRAEV, Rustem B.; KOZHOKOV, Mukhamed K.; CHERCHESOVA, Susanna K.; KOKAEVA, Fatima F.; TLETSERUK, Irina R. (Journal of Environmental Management and Tourism; Vol 8 No 3 (2017): JEMT Volume VIII Issue 3(19) Summer 2017, 2017)
Metallurgical enterprises are the main source of environmental pollution with heavy metals. Toxicants pose a serious threat to the consumer’s health, so scientific research on diminishing their adverse effect on sanitary-hygienic properties of poultry meat is of high importance when organizing effective environmental management and ensuring food security. The purpose of the study is to devise a method for reducing a negative impact of heavy metals on productivity and sanitary-hygienic properties of meat by admixing adsorbents to a formulation of animal feeds. To analyse the concentration of heavy metals, the atomic adsorption method was applied. Experimental data were statistically processed using SNEDECOR application package. The findings of the research suggest that the prudent use of the adsorbents such as citrus pectin and Toxiban Max in the formulation of local barley-corn-soybean based feeds allowed maximizing the effect of heavy metal detoxification. The concentration of these elements in meat of the experimental groups of broilers was lower than the maximum allowable level.